2022
DOI: 10.2340/17453674.2021.1080
|View full text |Cite
|
Sign up to set email alerts
|

Continuous periprosthetic bone loss but preserved stability for a collum femoris-preserving stem: follow-up of a prospective cohort study of 21 patients with dualenergy X-ray absorptiometry and radiostereometric analysis with minimum 8 years of follow-up

Abstract: Background and purpose — We previously described a decrease in bone mineral density (BMD) in the calcar region 2 years after insertion of the collum femoris-preserving (CFP) stem, but the implants were stable. Now we have examined the long-term changes in periprosthetic BMD and stability of the CFP stem. Patients and methods — We conducted a minimum 8-year follow-up of 21 patients from our original investigation. We examined periprosthetic BMD by dual-energy X-ray absorptiometry (DEXA) and implant stability by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The HOOS is a disease-specific PROM for patients undergoing THA but is not extensively used in the literature. Another commonly used PROM is the HHS, for which similar results were founded in our trial [12][13][14][15]. The MCII and PASS for the EQ5D are both achieved by patients in our trial [24].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The HOOS is a disease-specific PROM for patients undergoing THA but is not extensively used in the literature. Another commonly used PROM is the HHS, for which similar results were founded in our trial [12][13][14][15]. The MCII and PASS for the EQ5D are both achieved by patients in our trial [24].…”
Section: Discussionsupporting
confidence: 82%
“…No strong conclusions can be drawn on implant survival because this trial was not statistically powered for survival analysis. When looking at observational studies, we also see higher revision rates for the CFP than for the Zweymüller stem [11][12][13][27][28][29][30]. Although not statistically significant, our RCT supports these findings.…”
Section: Strengths and Limitationssupporting
confidence: 61%
See 1 more Smart Citation
“…In the rectangular CFP prosthesis, the average stress shielding rate is 5.6% (4.1%–6.7%), while in the circular CFP prosthesis, the average stress shielding rate is as high as 35% (5.2%–66%) 19–25 . In the latest prospective cohort study, 21 patients who underwent THA with CFP prosthesis were followed up for at least 8 years, and the results of the 2‐year follow‐up showed that the bone loss at the top of the femur continued for 8 years 26 . The authors believed that the CFP prosthesis could not prevent bone absorption around the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] In the latest prospective cohort study, 21 patients who underwent THA with CFP prosthesis were followed up for at least 8 years, and the results of the 2-year follow-up showed that the bone loss at the top of the femur continued for 8 years. 26 The authors believed that the CFP prosthesis could not prevent bone absorption around the prosthesis.…”
Section: Analysis Of Design Defects and Failure Causes Of Cfp Prosthesismentioning
confidence: 99%